EVALUATION OF IN VITRO ANTIPLASMODIAL ACTIVITY OF ICACINA OLIVIFORMIS’S (STEMS AND ROOTS) AND SPONDIAS PURPUREA’S (LEAVES, BARKS AND ROOTS) EXTRACTS FROM ZIGUINCHOR, SENEGAL (World Journal of Current Medical and Pharmaceutical Research, 2019)
This study was designed to assess phytochemical and antiplasmodial activities of Icacina oliviformis’s and Spondias purpurea’s extracts. Icacina oliviformis (poiret) Raynal (Icacinaceae) and Spondias purpurea L. (Anacardiaceae) are Senegalese traditional pharmacopoeia plants used to treat various diseases. These plants are used for treating malaria and related conditions in south Senegal.The following phytochemicals were detected into the two species: saponins, alkaloids, sterols, polyterpenes, polyphenols, flavonoids, tannins and free or combined quinones. As regards the evaluation of antiplasmodial activity against P. falciparum 3D7 strain, the ethanolic/water extract of Icacina oliviformis stems (SEWIO) displayed the best activity with an IC50 = 1.80 ± 0.51 μg/mL. Therefore, the same extract exhibits some degree of cytotoxicity with a CC50 = 78.30 ± 2.45 μg/mL. The antiplasmodial activity and the cytotoxicity of Icacina oliviformis’s (stems and roots) and Spondias purpurea’s (leaves, barks and roots) extracts are reported for the first time.